European Union and New Regionalism: Regional Actors and Global Governance in a Post-Hegemonic Era. Author: Mario Telo, Ashgate, 2007, 428 pages. ISBN: 978-0-7546-4991-5 - (:unkn) unknown (My University, 2009)
0
Keywords: Uluslararası İlişkiler; Siyasi Bilimler